Literature Review: Formulation of Work-Life Balance Against Environmental Dynamics - Putra, Surya Jaya Purnama; Ratnawati, Tri; Santi, Dyan Evita (International Journal of Research in Counseling, 2023)
The purpose of study This is For discuss possible strategies and formulations help individual reach balance life Work in face change sustainable environment changed . Research methods This use studies literature For analyze work-life balance based on study previously. Several strategies and formulations For increase balance life Work including flexibility time and place work , reduce demands work, use appropriate technology, develop habit life healthy, and get support from family and friends . In facing the dynamics change environmental , factors like technolog, demands work, and health must noticed For reach balance life healthy work. With apply appropriate strategies and formulations , individually can reach healthy balance between work and life personal.